Anaemia in under five children attending a tertiary hospital in central Kerala: a cross sectional study - Jose, Jessie; Lukose, Riya; Athira, Thekkumpat S. (International Journal of Contemporary Pediatrics, 2021)
Background: Anaemia is the most common nutritional problem in the world with significant impact on the neurological and cognitive development of young, growing children. India has a high prevalence of anaemia among its under-five children. The objectives of the study were to estimate the prevalence of anaemia and iron deficiency anaemia in children in the age group 6 months to 5 years. Methods: A hospital based descriptive study was done on 51 children attending the outpatient department of a tertiary hospital. They were evaluated by obtaining a detailed history, physical examination and haemoglobin and serum ferritin estimation. Results: The prevalence of anaemia in the present study was 41.2%. 13 (25.5%) had mild anaemia, 8 (15.7%) had moderate anaemia and none had severe anaemia. Iron deficiency anaemia was present in 17 out of 21 children (81%) with anaemia (p<0.00001). There were significant associations between haemoglobin levels and age (p=0.049) and nutritional status (moderate acute malnutrition) (p=0.034) of the children in the study. Conclusions: The prevalence of anaemia in children under 5 years in Kerala, which has performed well in other health quality indicators, remains high. A multimodal strategy to address this public health problem is required.